2023
DOI: 10.1111/nph.19080
|View full text |Cite
|
Sign up to set email alerts
|

E3 ligase ATL5 positively regulates seed longevity by mediating the degradation of ABT1 in Arabidopsis

Abstract: Summary Ubiquitination is a fundamental mechanism regulating the stability of target proteins in eukaryotes; however, the regulatory mechanism in seed longevity remains unknown. Here, we report that an uncharacterized E3 ligase, ARABIDOPSIS TÓXICOS EN LEVADURA 5 (ATL5), positively regulates seed longevity by mediating the degradation of ACTIVATOR OF BASAL TRANSCRIPTION 1 (ABT1) in Arabidopsis. Seeds in which ATL5 was disrupted showed faster accelerated aging than the wild‐type, while expressing ATL5 in atl5‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…In contrast, it remains highly expressed in embryos of mature seeds and reproductive organs. Taken together, these findings highlight the involvement of ATL5 in the regulation of ABT1-mediated transcriptional activation associated with seed longevity and provide an initial insight into the role of RING E3s in directly modulating basal transcriptional activation in the context of seed longevity …”
Section: Atls In Plant Growth and Developmentmentioning
confidence: 60%
See 2 more Smart Citations
“…In contrast, it remains highly expressed in embryos of mature seeds and reproductive organs. Taken together, these findings highlight the involvement of ATL5 in the regulation of ABT1-mediated transcriptional activation associated with seed longevity and provide an initial insight into the role of RING E3s in directly modulating basal transcriptional activation in the context of seed longevity …”
Section: Atls In Plant Growth and Developmentmentioning
confidence: 60%
“…Both in vivo and vitro assessments demonstrated that ATL5 functions as an E3, orchestrating polyubiquitination and subsequent degradation of ABT1. 62 Disruption of ATL5 function impeded the degradation of synthesized ABT1, while the degradation process was inducible through seed aging and followed a proteasome-dependent mechanism. Additionally, the disruption of ABT1 was associated with an increase in seed longevity.…”
Section: Atls In Plant Growth and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice mutants with reduced anti-oxidant levels displayed reduced seed longevity. These plants exhibited increased expression of an E3 ubiquitin ligase of ARABIDOPSIS TOXICOS EN LEVADURA family and the Arabidopsis orthologue, ATL5, was shown to be required for seed longevity, potentially acting as a regulator of transcription [ 93 ]. Changes in protein phosphorylation have been reported in imbibing seeds [ 94 ], although the effects of ageing on post-translational modifications are less well characterised, other than oxidative products that are abundant in aged seeds [ 34 , 95 ].…”
Section: Cellular Responses To Seed Ageingmentioning
confidence: 99%
“…This process involves catalysis by three enzymes comprising E1 (ubiquitin‐activating enzyme), E2 (ubiquitin‐conjugating enzyme) and E3 (ubiquitin ligase) (Moon et al ., 2004 ; Qin et al ., 2008 ; Smalle and Vierstra, 2004 ). The diversity of E3 ubiquitin ligase confers specificity to the substrate protein selected, which plays a key role in the ubiquitination process (He et al ., 2023 ; Stone et al ., 2005 ; Xu and Xue, 2019 ; Yu et al ., 2013 ). AtPUB1 acts as an E3 ubiquitin ligase and degrades the receptor‐like protein kinases LRR1 and KIN7, thereby negatively regulating the response of Arabidopsis thaliana to drought stress (Chen et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%